Designing a Model for Efficient Human Resource Training from the Perspective of Islamic Education - Gholampour, Hossein; Mashinchi, Ali Asghar; Ranjbar, Mokhtar (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The aim of this research is to design a model for efficient human resource training based on Islamic education principles.Methodology: The research methodology is qualitative and is based on the deductive content analysis method. The research domain includes content analysis of Quranic verses and Hadiths, as well as all books and resources written on the topic of human resource training. The sampling method is purposive. Data collection was conducted using note-taking from relevant books and resources. The data analysis method is content analysis using a deductive categorization system. For this purpose, a three-stage thematic coding method was used, and the data were analyzed using open, axial, and selective coding. Finally, the model was presented. In this research, credibility criteria were used to examine validity, and reliability criteria were used to ensure dependability.Findings: The results indicate that the model for efficient human resource training from the perspective of the educational system of the Infallible Imams (PBUH) is based on individual, social, and political characteristics derived from approximately 204 initial concepts or free codes and 16 axial categories. It includes components such as 1) religious knowledge and awareness, 2) creativity and knowledge in the work domain, 3) competence, 4) efficiency in management, 5) courage, 6) decisiveness, 7) humility and avoidance of arrogance, 8) faith and belief in the goal, 9) adherence to responsibility, 10) a clean past with no misconduct, 11) social justice, 12) social interaction with intellectuals, 13) understanding societal conditions and enduring hardships, 14) responsibility and initiative in action, 15) simplicity and being a role model, and 16) political insight and outlining general policy lines. Additionally, the model for efficient human resource training from the perspective of the educational system of the Infallible Imams (PBUH) is based on educational methods such as appropriate response, punishment and encouragement, tolerance and decisiveness, and exemplary methods derived from approximately 90 initial concepts or free codes and 14 axial categories. It includes components such as 1) effective response, 2) timely reaction, 3) reward, 4) encouragement, 5) decisive reaction, 6) reprimand, 7) supervision and control, 8) overt supervision, 9) covert supervision, 10) public supervision, 11) tolerance, 12) firmness and decisiveness, 13) modeling, and 14) modeling the behavior of the Infallible Imams (PBUH).Conclusion: The explained model addresses all educational principles and can create conditions for efficient human resource training in trainers and educators by applying the suggested methods.